Prognostic and predictive value of loss of nuclear RAD51 immunoreactivity in resected non-small cell lung cancer patients. (March 2017) - Gachechiladze, Mariam; Škarda, Josef; Kolek, Vítězslav; Grygárková, Ivona; Langová, Kateřina; Bouchal, Jan; Kolář, Zdeněk; Baty, Florent; Stahel, Rolf; Weder, Walter; Soltermann, Alex; Joerger, Markus
Highlights: Prognostic and predictive value of RAD51 protein loss has been assesed. Loss of RAD51 is unfavourable prognostic factor in early stage resected NSCLC. Loss of RAD51 is favourable in patients receiving perioperative Chemo-/Radiotherapy. Abstract: Objectives: In response to DNA damage, recombination proteins are relocalized into sub-nuclear complexes that are microscopically detected as RAD51-containing nuclear foci. We aimed for assessing the prognostic and predictive value of loss of nuclear RAD51 immunoreactivity ('RAD51 loss') in 2 independent stage I to III non-small cell lung cancer (NSCLC) patient cohorts undergoing surgical resection and eventual perioperative chemo-/radiotherapy (CT/RT). Materials and methods: The discovery set included 69 evaluable patients (19 adenocarcinomas, ADC, 50 squamous cell carcinomas, SCC) from Palacky University Hospital, 45/69 (65.2%) with additional platinum-based CT. The replication set entailed 845 evaluable patients (446 ADC, 399 SCC) from University Hospital Zurich, 308/845 (36.5%) with platinum based CT or RT. RAD51 loss was defined as ≤20% of tumor cell nuclei having any nuclear RAD51 expression. We assessed the prognostic value of RAD51 loss in all patients and its predictive value in patients receiving CT/RT. Results: RAD51 loss was observed in 40/69 (58.0%) and 439/845 (51.9%) evaluable tumors in the discovery and replication set, respectively (p = 0.34). It was more frequent in ADC compared to SCC (57.2% vs 47.4%, p = 0.003). RAD51 loss was significantly associated with worse OS in both the discovery (adjusted HR = 2.39, p = 0.039) and replication set (adjusted HR = 1.31, p = 0.008). The unfavourable prognostic effect of RAD51 loss seen in the overall population was not observed in patients receiving perioperative CT (adjusted HR = 1.07, p = 0.73) or perioperative RT (adjusted HR = 1.05, p = 0.82). Conclusion: RAD51 loss has an unfavourable prognostic impact in NSCLC patients undergoing curative surgical resection, but it may have a favourable predictive value in the subgroup of patients receiving perioperative platinum-based CT or RT, most likely as a consequence of deficient DNA repair.